Antibacterial Activity of Live Cells of Lactobacillus Plantarum L40 as A Probiotic Against Pathogens Associated with Diabetic Foot Infections - AlAsadi, Haneen Majid Abdulkareem; Luti, Khalid Jaber Kadhum (Iraqi Journal of Science, 2023)
The present study was designed to select a suitable isolate of Lactobacillus sp. in order to use it as a probiotic formula for treating diabetic foot ulcer disease in diabetic mellitus patients. In order to determine the inhibitory action, 240 isolates of Lactobacillus from different sources, were taken and exposed for screening tests to evaluate the (antagonism-activities) toward 4 multi-drug resistant foot ulcer pathogens which were chosen from 120 pathogenic isolates: Staphylococcus aureus, Klebsiella pneumonia, Proteus mirabilis, and P. aeruginosa. Twenty Lactobacillus isolates were selected from primary screening according to the capacity to restrain its expansion of four markers, that were exposed toward second screenings to detect their ability to produce a high amount of bacteriocin. Based on the results, the isolate Lactobacillus L40 was selected as the highest bacteriocin producing isolate which was further characterized as Lactobacillus plantarum Next, several tests were performed to study the properties of L. plantarum L40, in particular its biosafety and its suitability to be a successful probiotic. Results showed that L. plantarum was resistant to cephalosporin groups such as ceftriaxone and cefepime whereas, it was sensitive to amikacin and chloramphenicol. In addition, results revealed that this bacterium was strongly adherent and a good biofilm producer; had high auto-aggregation capability and a high ability to adhere with S. Staphylococcus aureus, Klebsiella pneumonia, Proteus mirabilis and P. aeruginosa. A gel formula containing live cells of L. plantarum L40 was prepared and based on the results, cells were successfully survived in this formula over 18 days. Therefore, it was selected to be utilized as a vector to store and transport viable cells of L. plantarum L40. This gel formula showed antibacterial activity by inhibiting Staphylococcus aureus, Klebsiella pneumonia, Proteus mirabilis, and P. aeruginosa growth. The results showed the possibility of using viable cells of bacteriocin-producing Lactobacillus plantarum as an effective probiotic to deal with some skin pathogens, and hence treat skin diseases such as diabetic foot ulcer disease.